The Effect of Perceived Ease of Use Through Perceived Enjoyment on Behavioral Intention Among GoPay E-Wallet Users (Case Study of Warmadewa University Students) - Gusti Ayu Sugiati; Ni Ketut Widiantari; Ketut Sudarmini (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of Perceived Ease of Use on Behavior Intention through Perceived Enjoyment on Behavior Intention in GoPay e-wallet users, a case study of Warmadewa University students. E-wallet has become an increasingly popular digital payment method among the younger generation because of the ease and convenience it offers. The research method used is quantitative with a stratified random sampling technique, resulting in 67 respondents from various study programs at Warmadewa University. Data analysis was carried out using Structural Equation Modeling (SEM), Partial Least Squares (PLS) with SmartPLS software. The results of the study show that: (1) Perceived Ease of Use has a positive and significant effect on Perceived Enjoyment. (2) Perceived Ease of Use has a positive and significant effect on Behavior Intention. (3) Perceived Enjoyment is proven to partially mediate the relationship between Perceived Ease of Use and Behavior Intention. These findings indicate that the ease of use of the GoPay application increases user convenience, which ultimately drives their intention to continue using the application.